Digital Laser Micropainting for Reprogrammable Optoelectronic Applications - Lee, Younggeun; Kwon, Jinhyeong; Lim, Jaemook; Shin, Wooseop; Park, Sewoong; Hwang, Eunseung; Shin, Jaeho; Cho, Hyunmin; Jung, Jinwook; Kim, Hyun Jong; Han, Seungyong; Lee, Habeom; et al. (Advanced Functional Materials, 2021)
Structural coloration is closely related to the progress of innovative optoelectronic applications, but the absence of direct, on-demand, and rewritable coloration schemes has impeded advances in the relevant area, particularly including the development of customized, reprogrammable optoelectronic devices. To overcome these limitations, a digital laser micropainting technique, based on controlled thin-film interference, is proposed through direct growth of the absorbing metal oxide layer on a metallic reflector in the solution environment via a laser. A continuous-wave laser simultaneously performs two functions—a photothermal reaction for site-selective metal oxide layer growth and in situ real-time monitoring of its thickness—while the reflection spectrum is tuned in a broad visible spectrum according to the laser fluence. The scalability and controllability of the proposed scheme is verified by laser-printed painting, while altering the thickness via supplementary irradiation of the identical laser in the homogeneous and heterogeneous solutions facilitates the modification of the original coloration. Finally, the proof-of-concept bolometer device verifies that specific wavelength-dependent photoresponsivity can be assigned, erased, and reassigned by the successive application of the proposed digital laser micropainting technique, which substantiates its potential to offer a new route for reprogrammable optoelectronic applications.
Keywords: Metal oxide layers; Metallic reflectors; Optoelectronic applications; Photoresponsivity; Photothermal reactions; Real time monitoring; Reflection spectra; Thin-film interference; hydrothermal growth; laser; reprogrammable optoelectronics; structural coloration; thin-film interference